Aplicação de pó de rocha e enxofre elementar associado a plantas de cobertura do solo, na disponibilidade de nutrientes para a cultura do milho - Reis, Willian dos (2020)
In agriculture, decreasing fertilization costs with the use of alternative sources can make the agricultural sector more competitive and sustainable. Alternatives such as rock dust can be an important tool for improving soil fertility, especially in agroecological agriculture. The objective was to evaluate the effect of the application of rock dust and elemental sulfur associated with cover crops, on soil attributes and on corn productivity. The experimental design was in randomized blocks in a subdivided plot scheme, with four replications. The main plots consisted of three soil coverings: consortium of black oats and turnip, turnip and uncovered soil. The subplots were composed of the presence or absence of rock dust: 12 t ha-1, with the sub-plots having the presence or absence of elemental sulfur: 60 kg ha-1. The dry matter productivity of the cover plants was evaluated; volumetric humidity and resistance to soil penetration; accumulation of nutrients by cover crops; leaf nutritional contents, yield components and corn productivity. The monoculture turnip provided dry matter accumulation 70% higher than that accumulated by the consortium of black oats and forage turnip; also promoting less resistance to penetration in the 0.0-0.2 m layer; as well as greater N accumulation in the corn leaf tissue. The consortium (forage turnip + black oats) promoted an increase of 1.7% in the volumetric moisture of the soil in relation to the area maintained without cover; the consortium of black oats and forage turnip presented accumulation of 21% of N, 19% of P, 89% of Mn, 334% of Fe and 86% of Cu, superior to the monoculture of forage turnip; the application of rock dust associated with the application of elemental sulfur provided greater accumulation of Fe in the leaf tissue of corn; the rock powder associated with the intercrop and sulfur promoted less accumulation of Mg in the leaf tissue of corn; maize productivity did not increase by cultivating cover crops, applying rock dust and using elemental sulfur.